2023
DOI: 10.3389/fpubh.2023.1165753
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental activities of daily living trajectories and risk of mild cognitive impairment among Chinese older adults: results of the Chinese longitudinal healthy longevity survey, 2002–2018

Abstract: BackgroundThe association between the instrumental activities of daily living (IADL) score and the risk of initial cognitive function impairment is inconclusive. We aimed to identify distinctive IADL trajectories and examine their relationship with the onset of mild cognitive impairment (MCI) among Chinese older people.MethodsThe study used six-wave longitudinal data from the Chinese Longitudinal Healthy Longevity Survey conducted between 2002 and 2018. It included a total of 11,044 Chinese people aged 65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…The findings of this study are in line with earlier studies that have classified IADL disability trajectories into three categories [ 16 , 31 ]. However, a previous analysis of CHARLS data from 2011 to 2018 using group-based modeling identified three typical BADL disability trajectories [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study are in line with earlier studies that have classified IADL disability trajectories into three categories [ 16 , 31 ]. However, a previous analysis of CHARLS data from 2011 to 2018 using group-based modeling identified three typical BADL disability trajectories [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…To determine the best-fitting discrete number and pattern of ADL score trajectories, we used group-based trajectory modeling (GBTM), which is increasingly applied in healthy aging research [ 30 , 31 ]. The time metric was the years since baseline (2015–2022), and six waves of ADL scores were used to estimate the trajectory.…”
Section: Methodsmentioning
confidence: 99%
“…A plethora of modifiable and nonmodifiable risk factors that are associated with cognitive impairment among Chinese older adults have been identified. Previous studies have found that increased age, limited functional independence, alcohol consumption, hypertension, and depression are significantly associated with cognitive impairment [ 3 9-12 undefined undefined undefined ]. Protective factors have also been identified, namely, good sleep quality, sleeping sufficiently for many hours per night, exercise, and increased social participation [ 3 9 13-17 undefined undefined undefined undefined ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a study identified three combined profiles of BADL and IADL employing latent profile analysis (LPA) among elderly individuals in China [ 6 ]. Another study using a group-based trajectory model demonstrated the dynamic changes of IADL over time, which could be divided into three trajectories [ 20 ]. Both studies demonstrated the differences in IADL among elderly individuals based on latent variable modeling, which may be attributed to various demographic characteristics such as age [ 12 ], health conditions [ 13 ], and their changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Second, most studies have been cross-sectional in nature. Although longitudinal studies have demonstrated the existence of three distinct developmental trajectories for IADL [ 20 ], the probability of transitions in the state of IADL over time remains unclear. To address these limitations, latent transition analysis (LTA) may offer a promising solution.…”
Section: Introductionmentioning
confidence: 99%